Identification of one novel pathogenic ITGB3 mutation and two known mutations in two Chinese pedigrees with hereditary Glanzmann thrombasthenia. (2nd April 2020) - Lu, Zhengjing; Nikuze, Lauriane; Zhong, Zhoulin; Li, Fang; Zhang, Fuyong; Liang, Kairong; Wei, Manlv; Wei, Hongying
Abstract: Glanzmann thrombasthenia (GT) is an inherited disorder of platelet aggregation resulting from quantitative and/or qualitative abnormalities of the glycoprotein IIb/IIIa complex. We analyzed the expression of GPIIb/IIIa and the gene sequencing in two pedigrees with GT, so as to determine the type and the relationship between genotype and clinical phenotype. Platelet aggregation tests and flow cytometric studies were performed, along with gene sequencing. Both probands were classified as grade III of bleeding. Platelet aggregation was absent or defective upon stimulation with physiological stimuli like AA and ADP, but platelets agglutinated normally in response to ristocetin. MFI values were considerably reduced. Gene sequencing showed ITGB3 mutations p.Cys549Ser/p.Leu705CysfsTer4 in proband 1 and p.Cys549Ser/p.Gln254Lys in proband 2 and her sister. This study reports one novel ITGB3 mutant gene, p.Gln254Lys, of which we will explore the potential pathogenicity.